Nanostructured Conductive Metal Organic Frameworks for Sustainable Low Charge Overpotentials in Li–Air Batteries. Issue 4 (10th December 2021) - Majidi, Leily; Ahmadiparidari, Alireza; Shan, Nannan; Kumar Singh, Sachin; Zhang, Chengji; Huang, Zhehao; Rastegar, Sina; Kumar, Khagesh; Hemmat, Zahra; Ngo, Anh T.; Zapol, Peter; Cabana, Jordi; et al.
Abstract: Lithium–oxygen batteries are among the most attractive alternatives for future electrified transportation. However, their practical application is hindered by many obstacles. Due to the insulating nature of Li2 O2 product and the slow kinetics of reactions, attaining sustainable low charge overpotentials at high rates becomes a challenge resulting in the battery's early failure and low round trip efficiency. Herein, outstanding characteristics are discovered of a conductive metal organic framework (c‐MOF) that promotes the growth of nanocrystalline Li2 O2 with amorphous regions. This provides a platform for the continuous growth of Li2 O2 units away from framework, enabling a fast discharge at high current rates. Moreover, the Li2 O2 structure works in synergy with the redox mediator (RM). The conductivity of the amorphous regions of the Li2 O2 allows the RM to act directly on the Li2 O2 surface instead of catalyst edges and then transport through the electrolyte to the Li2 O2 surface. This direct charge transfer enables a small charge potential of <3.7 V under high current densities (1–2 A g −1 ) sustained for a long cycle life (100–300 cycles) for large capacities (1000–2000 mAh g −1 ). These results open a new direction for utilizing c‐MOFs towards advanced energy storage systems. Abstract : The catalytic performance of copper tetrahydroxyquinone conductive metal organic framework (C‐MOF) is studied in a Li–air battery. The C‐MOF promotes formation of nanocrystalline Li2 O2 embedded in amorphous regions. This property in combination with InBr3 enables a battery operation under a high current density with a highly stable and reduced charge overpotential, a well‐retained discharge capacity and a long cycle life.